How pre-service teachers can be supported to increase their diagnostic skills in mathematics—design and evaluation of a learning platform for university teacher training - Walter, Daniel; Bergmann, Andreas; Maibach, Meike; Huethorst, Lara; Reinartz, Lea; Grünewald, Nina; Selter, Christoph; Harrer, Andreas (Frontiers in Education, 2025)
One key training objective of pre-service teachers is to develop their diagnostic skills in order to enable them to support their students adequately. This article describes the conception and evaluation of the digital learning platform FALEDIA. Researchers from different perspectives of mathematics education on the one hand and of computer science on the other report on design principles and concrete realizations which intend to support the needs of the targeted user group. A pre-post-test about diagnostic skills with 695 pre-service teachers from two universities provides insights into their gains of knowledge. A questionnaire about learning styles was conducted and the pre-service teachers’ interactions with the digital learning plattform were tracked to get insights into their usage of the FALEDIA plattform. It is shown that pre-service teachers—from first-year to experienced—achieved significant performance gains in terms of diagnostic skills through the learning platform. With regard to usage, it could be shown that the self-assessed learning style has only little effect on usage behavior.